Mechanical and wear characteristics of glass fiber reinforced modified epoxy nano composites – A review. (2021) - Jeyakumar, R.; Ramamoorthi, R.; Balasubramanian, K.
Abstract: Polymer nanocomposites have observed massive development in modern era due to their possible applications in a wide range of engineering industries. It is prominent that the combinations of nano fillers with polymer matrix offer materials with excellent properties, which are not feasible by using an individual element. The investigation on mechanical properties such as tensile strength, flexural strength, impact strength, micro hardness, interlaminar shear strength and compression strength was carried out for the manufactured reinforced composites. The dry Sliding wear test carried out by using pin on disc apparatus. It is proved that the wear loss was increased proportionally with load and sliding velocity. The morphological behaviour was examined by the use of scanning electron microscope for visualizing the uniform and homogeneous dispersion of nanoclay into the epoxy matrix. The homogeneity dispersion of the nanoclay is confirmed from the Scanning Electron Microscope (SEM) examination.